Ambipolar Carrier Mobility in Binary Blend Thin Film of Non-Peripheral Alkylphthalocyanines. (April 2016) - Fujii, Akihiko; Nakano, Shohei; Fukui, Hitoshi; Saito, Takashi; Ohmori, Masashi; Shimizu, Yo; Ozaki, Masanori
Abstract: Charge carrier mobility in blend films of two types of soluble phthalocyanine derivatives with different substituent length, 1, 4, 8, 11, 15, 18, 22, 25-octapentyl-phthalocyanine (C5PcH2 ) and 1, 4, 8, 11, 15, 18, 22, 25-octahexyl-phthalocyanine (C6PcH2 ) has been investigated. The charge carrier mobility was measured by the time-of-flight technique. In the case of C5PcH2 blend ratio below 25 mol%, the high mobility, such as 0.8-1.1 cm 2 V -1 s -1 for hole and 0.6 cm 2 V -1 s -1 for electron, were obtained at room temperature. In the thin films with C5PcH2 above 30 mol%, the charge carrier mobility decreased by one order of magnitude and had the different temperature dependence from that below 25 mol%. The marked change of the charge carrier mobility depending on the blend ratio of phthalocyanine derivatives has been discussed by taking the miscibility and the molecular packing structure into consideration.